Population Pharmacokinetics and Pharmacodynamics of Gabapentin After Administration of Gabapentin Enacarbil. (14th June 2013) - Lal, Ritu; Sukbuntherng, Juthamas; Luo, Wendy; Tovera, James; Lassauzet, Marie Liesse; Cundy, Kenneth C.
Abstract: Gabapentin enacarbil (GEn) is an actively transported prodrug of gabapentin that provides sustained dose‐proportional exposure to gabapentin and predictable bioavailability. Gabapentin enacarbil is approved by the US Food and Drug Administration for the treatment of moderate‐to‐severe primary restless legs syndrome (RLS) in adults. Using plasma gabapentin concentration data obtained after administration of GEn in 12 phase 1 to 3 GEn studies in healthy adults or patients with RLS (dose range, 300‐2400 mg/d), a population pharmacokinetic (PK) model was developed by nonlinear mixed‐effect modeling using NONMEM. Data were similar in subjects with and without RLS. Population PK‐pharmacodynamic (PD) models were evaluated using gabapentin exposure and change from baseline in investigator‐ or patient‐rated Clinical Global Impression of Improvement (CGI‐I) or International Restless Legs Scale (IRLS) total score. Potential PK‐PD models for sleep outcomes and safety parameters were also explored. The CGI‐I response increased with increasing GEn dose, whereas the IRLS total score was similar at all exposures tested. Early adverse events of dizziness or somnolence/sedation were more frequent for GEn 600 mg than higher doses; however, this is confounded by the fact that all subjects received the 600‐mg dose for 3 days prior to titration to higher dosages.